Monitoring performance in women's canoe polo athletes: An investigation using wearable technologies - Vastola, R.; Serra, E.; Benincasa, M. T.; De Martino, M. U.; Albano, D. (Journal of Physical Education and Sport, 2024)
Canoe polo is a rapidly growing and dynamic sport, yet its performance metrics remain underexplored. This pilot study aims to analyze the kinematic and physiological parameters of female canoe polo players during a simulated match using wearable technologies, specifically K-Sport GPS devices. Data were collected from 10 athletes on the Italian national team with K-AI Wearable Tech devices, which recorded key metrics including distance covered, speed, acceleration, and heart rate. The athletes covered an average distance of 545.1 m (± 60.80), with a peak speed averaging 3.03 m/s (± 0.26). Their maximum acceleration averaged 2.37 m/s2 (± 0.26), while maximum deceleration averaged -3.75 m/s2 (± 0.71). The average maximum heart rate was 168.6 bpm (± 11.38), and the average heart rate was 144.5 bpm (± 16.83), representing 75.2 % (± 8.57) of the theoretical maximum heart rate. These results suggest that canoe polo is a high-intensity, intermittent sport characterized by periods of moderate speeds (0 - 1 m/s) and bursts of activity at intermediate speeds (1 - 2 m/s). Brief, rapid accelerations and decelerations are essential for optimal performance in canoe polo, requiring well- developed anaerobic and aerobic energy systems. This study offers valuable insights for optimizing training programs and game strategies for female canoe polo players. It underscores the utility of wearable devices in monitoring and improving performance by providing objective and accurate data, enabling personalized training. Overall, the findings highlight the need for tailored training programs that enhance both anaerobic and aerobic capacities to enhance performance in this sport.